NEW VAPOR DEPOSITED DIELECTRIC POLYMER THIN FILMS FOR ELECTRONIC APPLICATIONS - SCHRÖDER, Stefan; MAGARIU, Nicolae; STRUNSKUS, Thomas; ABABII, Nicolai; LUPAN, Oleg; FAUPEL, Franz (Journal of Engineering Science (Chişinău), 2022)
Dielectric materials are of great interest in a vast amount of applications ranging from cable insulation to advanced electronic devices. The emerging trend of device miniaturization is creating an increased demand for dielectric thin films that can be produced precisely on the nanometer scale. In addition, special mechanical properties are often required, for example in the field of flexible organic electronics. Polymers are first-choice materials for this purpose. However, it is extremely difficult to produce precise nanoscale thin films, which have a low defect density and are free of e.g. residual solvent, by wet chemistry approaches. Initiated chemical vapor deposition (iCVD) is a solvent-free polymer thin film deposition process which can be used to produce high quality dielectric thin films with nanoscale control and circumvents thus these problems. This work demonstrates the versatility of the iCVD process in the field of electrical applications by some new application examples of iCVD. By adding e.g. a hydrophobic organosiloxane thin film on columnar zinc oxide (ZnO:Fe) gas sensing structures there was a change in the selectivity from ethanol to hydrogen, as well as improved performance at high humidity level. The modified sensors can thus be used in humid ambient, especially for breathing tests, which can lead to the diagnosis of some diseases by cutting edge non-invasive approaches.